2013
DOI: 10.1007/s11605-012-2113-1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Comparative Study Evaluating Learning Curves of Novices in a Basic Single-Incision Laparoscopic Surgery Task

Abstract: The results of this study indicate that the proficiency reached using a conventional laparoscopic set-up cannot be matched using a SILS configuration for the novice surgeon and that the choice of straight or articulated instruments as well as previous laparoscopic training does not confer an advantage in this basic task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Participants had received postgraduate training for an average of *2 years (min 1 year, max 4 years). To reduce possible bias due to previous experience (i.e., knowledge-based shortcuts), we involved only laparoscopically naive residents [17]. Most of the residents were junior surgical trainees (only two of them were middle surgical trainees).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants had received postgraduate training for an average of *2 years (min 1 year, max 4 years). To reduce possible bias due to previous experience (i.e., knowledge-based shortcuts), we involved only laparoscopically naive residents [17]. Most of the residents were junior surgical trainees (only two of them were middle surgical trainees).…”
Section: Participantsmentioning
confidence: 99%
“…The main limitations for subjectivebased methods rise in their off-line nature or the response biases related to personal and motivational factors [15]. Computer-based methods have very limited applicability outside expensive simulation laboratories [16,17]. Thus, the development of objective and feasible systems to assess surgical task load remains a major challenge in the healthcare field [18,19].…”
mentioning
confidence: 99%
“…Learning curves were generated for the 25 repetitions of the PEG task by employing methods previously described by Feldman et al 27 and used in similar studies. 28 This involved applying non-linear regression to an inverse curve of the data. Both "learning plateau" and "learning rate" were quantified from this.…”
Section: Statistics and Learning Curvementioning
confidence: 99%
“…Fransen et al [12] found that short-term box training significantly improved novice trainees’ basic skills in LESS. Sodergren et al [8] showed that prior training in conventional laparoscopy did not influence learning or proficiency in LESS for novice surgeons. These previous reports agree with our findings that prior surgical experience in laparoscopic surgery does not make it easier to obtain LESS proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al [7] demonstrated that previous laparoscopic experience improved the ability to perform LESS. In contrast, a comparative study evaluating the LESS learning curves of novices by Sodergren et al [8] found that prior training in conventional laparoscopy does not influence LESS learning or proficiency.…”
Section: Introductionmentioning
confidence: 97%